Enabling Interactive Music Performance through Web Browsers for non-Programmers - Neimog, Charles K.; Souza, Rodolfo Coelho de (Anais do Simpósio Brasileiro de Computação Musical, 2025)
We introduce pd4web, software that allows running Pure Data (Pd) patches directly in web browsers without programming expertise. It removes the need for C code or build configuration, enabling Pd-based electroacoustic and live-electronic works on desktop and mobile platforms. Unlike similar tools, pd4web targets musicians and composers familiar with Pd, allowing them to deploy patches online. By lowering technical barriers, it expands creative possibilities and reduces dependence on specialized hardware or software. pd4web has been used in compositions such as Improviso I, Cˆanticos de Sil´ıcio I, but also in projects like Gaiasenses Web and cartoP5, demonstrating real-time web-based electroacoustic performance with minimal setup. However, due to the Web Audio API and remaining challenges, including latency and performance limits, the need for ongoing improvements to the Web Audio API remains.